Военно-эстетическое воспитание будущих офицеров в ходе стажировки - Kurochkin E. A. (Pedagogical excellence and pedagogical technologies, 2016)
The article is devoted to the modern military education of the future officers of military service problem of formation of values in the educational process by acting on their emotional and sensual sphere. It seeks to discover the essence and content and pedagogical way the military and aesthetic education of the future officers in the course of military practice and training
Keywords: подготовка будущих офицеров; военно-эстетическое воспитание; военно-эстетические ценности; войсковая стажировка; войсковая практика; training of future officers; military-aesthetic bringing; military-aesthetic values; army training; army practice